Manajemen Pembelajaran di Sekolah Dasar Muhammadiyah Kedunggong - Janingsih; Rahmah Ayu Andini; Farid Setiawan (Jurnal Pendidikan Dasar Islam, 2023)
This research aims to describe learning management at SD Muhammadiyah Kedunggong, especially learning planning, learning implementation and learning assessment. This research is a qualitative research. This research was conducted at SD Muhammadiyah Kedunggong. This research was conducted on grade 5 teachers. Data collection methods included interviews, observations and notes. The research results show that learning planning is made in the form of a syllabus and lesson plans. The implementation of management in the classroom is able to create a classroom atmosphere as a learning environment that will develop the abilities of students such as the number of learning methods used so that students are conducive to their learning. In this approach activity, it is based on changing behavior in classroom management, this is described as a process that changes student behavior in the classroom. Not only that, but by providing evaluation activities the learning conditions will be better and you will be able to find out how far students' abilities have been improved.